Analisis kemampuan literasi digital Guru dalam pembelajaran - Ermiana, Ida; Fauzi, Asri; Jiwandono, Ilham Syahrul; Oktaviyanti, Itsna; Rahmatih, Aisa Nikmah (Universitas Muhammadiyah Magelang, 2024)
Digital literacy is one of the most important skills along with the development of education that emphasizes critical thinking skills, collaboration, communication, and creativity. Teachers are expected to be able to integrate digital technology into the learning process to make it more effective, interactive, and in accordance with the needs of students. The digital learning environment requires education actors to have adequate digital literacy competencies in order to create a conducive learning environment. Teachers as important actors in learning should have adequate digital literacy skills. This study aims to analyze the digital literacy skills of teachers at SDN 37 Ampenan and to find out what percentage of the digital literacy skills of teachers at SDN 37 Ampenan. The subjects of this study were fifteen teachers. The type of research is quantitative descriptive. The results of the questionnaire were analyzed and it was found that overall the digital literacy of teachers was in the good category. Seventy percent were categorized as good, thirty percent were categorized as very good, and zero percent were categorized as lacking and very lacking. Teacher digital literacy is the basic capital in learning, so that learning can be packaged and implemented according to global needs and challenges in the 4.0 era.